A clinical case of acute scrotal syndrome on the background of primary scrotal lipoma and literature review - Lim, Raymond Zhun Ming; Soo, Tze Hui; Mohamad Sharin, Mohamad Fairuz; Ilias, Aizat Sabri (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Primary scrotal lipomas are exceptionally uncommon entities within the scrotal sac frequently occur in younger males under 40. It usually painless and found incidentally during imaging. They are generally categorized based on their site of origin. Case presentation: A 36-year-old man presented with an acute onset of severe left scrotal pain at midnight. Clinical examination revealed two scrotal masses in the left hemiscrotum associated with excruciating tenderness on palpation and loss of cremasteric reflex. Ultrasonography showed a well-defined, oval-shaped, isoechoic lesion underlying the median raphe of scrotum alongside bilateral normal testes. Given the intensity of unexplained pain despite high dose of analgesia, urgent scrotal exploration was done. Intra-operatively, a yellowish, firm mass was identified at the upper pole of the left main testis which was excised. Histopathological examination revealed a primary scrotal lipoma with no necrotic area seen. Conclusions: Ultrasound is typically the first-line imaging technique to exclude more sinister pathology. The atypical presentation of excruciating pain mimicking testicular torsion in our case complicates the diagnostic process. Scrotal lipoma can be and should be excised as the standard treatment albeit found incidentally.